2014
DOI: 10.4028/www.scientific.net/amr.962-965.968
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influence of Rock Strength on Anchorage Performance of Resin Anchored Bolts

Abstract: Based on the introduction of the researches on the influence of the surrounding rock strength on the anchorage performance of resin anchored bolts at home and abroad, the numerical simulation was adopted to analyse anchorage system of single bolt support small-scale by using the finite difference program FLAC3D. The results showed that the stress distributions in resin capsules and surrounding rocks were different with the different strengths of surrounding rocks. The stresses in the surrounding rocks graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…e results show that the temperature has a great influence on the anchorage performance; the anchoring force of resin grout reaches its peak value when the temperature is at 25°C, and the increase or decrease of temperature will affect the anchoring force [7]. Aziz et al carried out a series of pullout tests and found that mixing time and bolt hole parameters have a significant impact on the anchoring force; approximately 10 s constitutes a suitable time for bolt installation; and the drilling of bolt holes contributes to improving load transfer capacity [8].…”
Section: Introductionmentioning
confidence: 94%
“…e results show that the temperature has a great influence on the anchorage performance; the anchoring force of resin grout reaches its peak value when the temperature is at 25°C, and the increase or decrease of temperature will affect the anchoring force [7]. Aziz et al carried out a series of pullout tests and found that mixing time and bolt hole parameters have a significant impact on the anchoring force; approximately 10 s constitutes a suitable time for bolt installation; and the drilling of bolt holes contributes to improving load transfer capacity [8].…”
Section: Introductionmentioning
confidence: 94%
“…Zhang et al simulated the resin anchor-hold at different temperatures and obtained the temperature around the drill hole can influence the resin anchor-hold [12]. Hu used a combination of laboratory tests and numerical simulation to study the effect of temperature on the anchoring properties of resin anchors [13]. To solve the problem of adaptability of the full-length anchorage agent technology and ensure the strength of the anchoring support in high ground temperatures, it is urgent to develop a new type of heat-resistant, high-strength, and full-length anchoring agent.…”
Section: Introductionmentioning
confidence: 99%
“…Huet al studied the influence of temperature on the anchoring performance of a resin anchor by combining a laboratory test and numerical simulation. e results showed that the anchoring force of the anchorage body was the largest at 25°C, and the anchoring force clearly decreased with the increase of simulated drilling temperature [12]. Based on the thick wall theory, Zhao and other researchers studied the relationship between anchor rib spacing and anchorage performance under different country rock conditions.…”
Section: Introductionmentioning
confidence: 99%